Some data on the isotopic composition of oxygen in the Sea of Azov waters. - Nikolayev, Sergey D; Naydin, D P (PANGAEA, 2001)
Data on oxygen isotope composition of waters from the Sea of Azov.
Part of the global seawater delta oxygen-18 database from reference Nikolayev 1976
Keywords: DEPTH, water; Nikolayev1976; OCE; Oceanography; Salinity; SESAME; Southern European Seas: Assessing and Modelling Ecosystem Changes; δ18O, water